Base‐Promoted Heterogeneous Reusable Copper Fluorapatite (CuFAP) Catalyzed Facile Synthesis of 1, 2‐Diarylethanols via C(sp3)‐H Functionalization of Nitrotoluene. Issue 2 (15th January 2018) - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R.
Abstract: A novel, an efficient protocol has been developed for the facile synthesis of various 1, 2‐diarylethanol in good to excellent yields via C(sp 3 )‐H functionalization of various nitrotoluenes with substituted aromatic, heterocyclic aldehydes/isatin. This is the first example in which base promoted heterogeneous, reusable copper fluorapatite (CuFAP) catalyzed C(sp 3 )‐H functionalization of various nitrotoluenes was achieved under ligand‐, additive‐ free reaction condition. The developed protocol is an environmentally benign approach, which replaces cumbersome protocols, avoids the use of costly precious metal catalysts, prefunctionalized substrates, and toxic reagents. The heterogeneous CuFAP catalyst was recovered by simple filtration and reused several times without the loss of its catalytic activity. The selective functional group transformation of 1, 2‐diaryethanol was accomplished. Abstract : Demonstrated first time a sustainable, green protocol for the efficient synthesis of various 1, 2‐diarylethanol via base promoted heterogeneous copper fluorapatite (CuFAP) catalyzed C(sp 3 )‐H activation/functionalization of various substituted nitrotoluenes with substituted aromatic, heterocyclic aldehydes/isatin.